2011
DOI: 10.1016/j.quascirev.2010.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary fire regimes of Australasia

Abstract: We have compiled 223 sedimentary charcoal records from Australasia in order to examine the temporal and spatial variability of fire regimes during the Late Quaternary. While some of these records cover more than a full glacial cycle, here we focus on the last 70,000 years when the number of individual records in the compilation allows more robust conclusions. On orbital time scales, fire in Australasia predominantly reflects climate, with colder periods characterized by less and warmer intervals by more biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(180 citation statements)
references
References 173 publications
4
176
0
Order By: Relevance
“…The charcoal and pollen records from the two deep sea cores 17 940 (taken by Sino-German joint cruise "SONNE-95" in 1994) (Sun et al, 2000) and 1144 (taken by ODP Leg 184 in 1999) (Luo et al, 2001) in the northern part of the South China Sea disclose that the high strength and frequency of natural fire corresponded to the drier climate during glacials or stadials. This relationship between climate and fire in the monsoon region of China is different from that at a global scale (Power et al, 2008;Daniau et al, 2010;Mooney et al, 2011), which may reveal that regional differences in climatic conditions determine vegetation type, fuel biomass, and fire weather. However, it provides regional evidence for understanding the relationship between climate and fire that may be different under different climate conditions.…”
Section: Climate Forcing On Fire Occurrencesmentioning
confidence: 97%
See 1 more Smart Citation
“…The charcoal and pollen records from the two deep sea cores 17 940 (taken by Sino-German joint cruise "SONNE-95" in 1994) (Sun et al, 2000) and 1144 (taken by ODP Leg 184 in 1999) (Luo et al, 2001) in the northern part of the South China Sea disclose that the high strength and frequency of natural fire corresponded to the drier climate during glacials or stadials. This relationship between climate and fire in the monsoon region of China is different from that at a global scale (Power et al, 2008;Daniau et al, 2010;Mooney et al, 2011), which may reveal that regional differences in climatic conditions determine vegetation type, fuel biomass, and fire weather. However, it provides regional evidence for understanding the relationship between climate and fire that may be different under different climate conditions.…”
Section: Climate Forcing On Fire Occurrencesmentioning
confidence: 97%
“…Palaeofire studies at global scales reveal that high fire activity occurred during warm interstadials or interglacials, and low fire activity occurred during cold stadials or glacials (Power et al, 2008;Daniau et al, 2010;Mooney et al, 2011). These studies consider that the overall reduction in biomass was a severe constraint on fire regimes during the glacial.…”
Section: Climate Forcing On Fire Occurrencesmentioning
confidence: 99%
“…The charcoal database presented by Mooney et al (2011) is the Australasian subset of a global charcoal database (Power et al, 2010) and contains all data sets (published and unpublished) up until 2011 that include charcoal analyses. The OZPACS working group under the Australasian Quaternary Association (AQUA) was created to investigate ecosystem changes and human impact on the landscapes over the last 500 years.…”
Section: Past Palaeoclimate Data Syntheses In Australasiamentioning
confidence: 99%
“…Peat is a promising archive within Australasia due to the large longitudinal coverage; mires are found from tropical locations in Papua New Guinea to the subantarctic islands (McGlone, 2002b;McGlone et al, 2010;Whinam and Hope, 2005). Most peat-based records in Australasia contain pollen and charcoal that may be used for palaeoclimate, palaeoecology, and palaeo-fire reconstructions (Whinam and Hope, 2005;Mooney et al, 2011). Degree of humification has also been applied as a hydroclimate indicator in the late Holocene (Burrows et al, 2014;Wilmshurst et al, 2002) in cores for which dating density is sufficient.…”
Section: Lakes Wetlands and Peatlandsmentioning
confidence: 99%
“…There has been a great deal of speculation about the supposedly pre-eminent role of ancient human populations in determining paleo-fire regimes [e.g., Flannery, 1994;Fowler and Konopik, 2007]. However, regional scale analyses have consistently failed to show an association between human presence or activities and the amount of biomass burning as shown by charcoal records [Daniau et al, 2010a;Mooney et al, 2011;Marlon et al, 2012;Power et al, in press]. The pre-industrial charcoal record of the past 2000 yrs parallels northern hemisphere temperature changes as reconstructed from multiple high-resolution natural archives [Marlon et al, 2008] and this same pattern has been independently demonstrated for the more recent period , on the basis of stable isotope analyses of carbon monoxide in Antarctic ice [Wang et al, 2010; see also Prentice, 2010].…”
Section: Introductionmentioning
confidence: 99%